Is Salmonella enterica shared between wildlife and cattle in cattle farming areas? An 11‐year retrospective study in Tokachi district, Hokkaido, Japan. Issue 2 (13th December 2021) - Yamaguchi, Emi; Fujii, Kei; Kayano, Mitsunori; Sakurai, Yoshie; Nakatani, Atsuko; Sasaki, Motoki; Hertl, Julia A.; Grohn, Yrjo T.
Abstract: Background: Salmonella enterica in cattle has long been problematic and suspected to be transmitted by wildlife in Tokachi, Hokkaido, a major cattle farming area in Japan. Understanding the role of wildlife in S. enterica transmission would be helpful for developing control strategies of bovine salmonellosis. Objectives: We aimed to elucidate the possibility of S. enterica transmission between sympatric wildlife, including raccoons and crows and cattle, in Tokachi from 2008 to 2018 by analysing S. enterica detection records, and the genetic relatedness of serotypes shared between wildlife and cattle. Methods: S. enterica detection records were based on the results of a field survey and existing cattle records at relevant organisations, including clinical reports, a monitoring survey and quarantine for introduced calves at growing farms and public calving farms. S. enterica was identified by polymerase chain reaction assay and serotyped by agglutination assay. The detection records were organised chronologically to investigate whether common serotypes in wildlife and cattle were detected in the same year. The isolates corresponding to detection records were assessed for their genetic patterns by pulsed‐field gel electrophoresis. Results: The prevalence of S. enterica in raccoons and crows was 10.7% (17/159) and 5.7% (55/967), respectively. The following serotypes were detected from both wildlife and cattle: Braenderup, Dublin, Infantis, Mbandaka, Montevideo, 4, [5], 12:i:‐ and Typhimurium. Genetically similar isolates for S . Braenderup, S . Dublin, S . Montevideo and S . 4, [5], 12:i:‐ were detected from both species in the same year. Conclusions: Our long‐term retrospective observations supported that S. enterica was shared between wildlife and cattle. Wildlife invasions should be controlled at farms to prevent inter‐species transmission of S. enterica from livestock farms. Abstract : Salmonella seemed to be shared between wildlife and cattle in cattle farming area, which was based on the occurrence records and genetic analysis.